2008
DOI: 10.1080/15563650701338237
|View full text |Cite
|
Sign up to set email alerts
|

Effects of adenosine receptor antagonists onamitriptyline-induced QRS prolongation in isolated rat hearts

Abstract: While 10(-4) M DPCPX shortened QRS prolongation, 10(-5) M CSC prolonged QRS duration in the isolated rat hearts with prolonged QRS duration induced by 5.5 x 10(-5)M amitriptyline. An adenosine A(1) receptor antagonist, DPCPX, might shorten amitriptyline-induced QRS prolongation by activating beta adrenergic receptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…In our previous isolated heart studies, we demonstrated that an amitriptyline infusion (5.5×10 −5 M) caused a significant prolongation of the QRS duration as an indicator of amitriptyline cardiotoxicity (18)(19). In the present study, the same dose of amitriptyline (5.5×10 −5 M) infusion was used to achieve amitriptyline cardiotoxicity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In our previous isolated heart studies, we demonstrated that an amitriptyline infusion (5.5×10 −5 M) caused a significant prolongation of the QRS duration as an indicator of amitriptyline cardiotoxicity (18)(19). In the present study, the same dose of amitriptyline (5.5×10 −5 M) infusion was used to achieve amitriptyline cardiotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…In control group (Group 1, n=5), isolated hearts were subjected to an infusion of 5% dextrose for 60 minutes. In our previous isolated rat heart studies, 5.5×10 −5 M amitriptyline infusion prolonged QRS duration by 50-75% (18)(19). In the amitriptyline group (Group 2, n=7), the same dose (5.5×10 −5 M) of amitriptyline was infused for 60 minutes to achieve amitriptyline toxicity.…”
Section: Experimental Protocolmentioning
confidence: 99%
See 2 more Smart Citations
“…In another study, Kalkan et al demonstrated that amitriptyline induced a vasodilation in the isolated rat aorta model via A 2a receptors, which suggests that adenosine A 2a -receptor stimulation seems to be partly responsible for amitriptyline-induced vasodilation and hypotension (Kalkan et al, 2007). Likewise, in an isolated rat-heart model, DPCPX, an adenosine A 1 -receptor antagonist, shortened amitriptyline-induced QRS prolongation (Akgun et al, 2008).…”
Section: Introductionmentioning
confidence: 97%